The Relationship of Education to the Trend of Fresh Graduates Working Comparison Before and During the Covid 19 Pandemic (In 2019 and 2020) in Indonesia: University of Indonesia (Jurnal Ekonomi dan Kebijakan Pembangunan, 2021)
The impact of the COVID-19 pandemic is very much felt by fresh graduates in the world, including in Indonesia. The number of fresh graduates with secondary and higher education who work has decreased in 2020 compared to 2019. The method used in this study is multilevel regression because it uses hierarchical data at the individual and macro levels. Controlled by individual characteristics and the Provincial Minimum Wage (UMP), the tendency to work for fresh graduates from college graduates increased in 2020 compared to 2019, but the tendency to work was still lower than high school graduates. Universities need to improve so that the graduates produced are in accordance with the needs in the job market. The quantity and quality of universities cannot be separated.